2020
DOI: 10.1101/2020.09.14.20194308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibodies to SARS-CoV-2 and risk of future sickness

Abstract: Background: The extent that antibodies to SARS-CoV-2 may protect against future virus-associated disease is unknown. Method: We analyzed 12928 healthy hospital employees for SARS-CoV-2 antibodies and compared results to participant sick leave records (Clinical trial registration: ClinicalTrials.gov NCT04411576). Results: Subjects with viral serum antibodies were not at excess risk for future sick leave (Odds Ratio (OR): 0.85 (95% Confidence Interval (CI) (0.85 (0.43-1.68)). By contrast, subjects with antibodi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…This study found a prevalence of 18% of IgG antibodies against SARS-CoV-2 among HCWs in a large cohort of HCWs from Stockholm, Sweden sampled during the later phases of the first wave of the epidemic. The seroprevalence was similar to the 19% reported among 2149 HCWs at Danderyd Hospital, a hospital of equivalent size in the Stockholm area [3], whereas Karolinska university Hospital demonstrated a lower seroprevalence of 12% among 12,928 HCWs [9]. Globally, seroprevalences among HCWs have ranged from 0 to 45.3% [6].…”
Section: Discussionsupporting
confidence: 73%
“…This study found a prevalence of 18% of IgG antibodies against SARS-CoV-2 among HCWs in a large cohort of HCWs from Stockholm, Sweden sampled during the later phases of the first wave of the epidemic. The seroprevalence was similar to the 19% reported among 2149 HCWs at Danderyd Hospital, a hospital of equivalent size in the Stockholm area [3], whereas Karolinska university Hospital demonstrated a lower seroprevalence of 12% among 12,928 HCWs [9]. Globally, seroprevalences among HCWs have ranged from 0 to 45.3% [6].…”
Section: Discussionsupporting
confidence: 73%
“…The seroprevalence was similar to the 19.1% reported among 2,149 HCWs at Danderyd Hospital, a hospital of equivalent size in the Stockholm area, 3 whereas Karolinska University Hospital demonstrated a lower seroprevalence of 11.5% among 12,928 HCWs. 9 Globally, seroprevalences among HCWs have ranged from 0% to 45.3%. 6 Residents in Stockholm had a seroprevalence of around 10% during the time of our study.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, the simultaneously enrolled reference group of employees without patient contact (n=3671) had a 9.7% seropositivity rate when tested by exactly the same serum test (OR for seropositivity when employed in home care services compared to the reference group: 2.3 (95% CI 1.8-3.1), p<0.0001, [12]).…”
Section: Resultsmentioning
confidence: 99%
“…As described in a parallel paper [12], we assembled a reference group of 3671 hospital employees that had no patient contact whatsoever. There were simultaneously enrolled at the Karolinska University hospital, also in Stockholm, Sweden.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation